Electronic structure of U2PtC2 and U2RhC2. (18th March 2015) - Ronning, F; Zhu, J-X
Abstract: We present density functional theory calculations within the generalized gradient approximation of U2 RhC2 and U2 PtC2 . We find the calculated density of states are significantly less than that measured by specific heat indicating the need for electronic correlations. The mass enhancement found for U2 PtC2 is m * /mband ≈ 4.